Проценка на поврзаноста помеѓу миопијата и глаукомот - Богданова, Ирина (Медицински факултет, УКИМ, Скопје, 2020)
Introduction: Glaucoma, one of the leading causes of irreversible blindness in the elderly population around the world, is a progressive optic neuropathy. Primary open angle glaucoma (PGCA) is the most common type of glaucoma among the population according to recent studies. Myopia or shortsightedness is a refractive anomaly in which the parallel light rays coming from a distance through the cornea and lens are focused in front of the retina in the vitreous and then in a state of divergence, forming in the retina ruptured circles. Knowing the predictors of glaucoma is of particular importance for making timely and proper decisions about appropriate treatment. Objectives: The primary objective of this study is to evaluate the association of myopia with glaucoma. The other objectives are: to determine whether a particular type of myopia is a higher risk factor for glaucoma than others, to evaluate the degree of glaucomatous changes with type of myopia, to determine the influence of certain parameters as risk factors for glaucoma. Materials and Methods: A retrospective (case-control) study was preformed with participation of patiens aged 25 to 70 years . The study was conducted in University Eye Clinic in Skopje in the glaucoma cabinet during 2015-2019. The study include 100 patients, 60 patients diagnosed with glaucoma, and 40 patients without diagnosed glaucoma.From the total number of patients,60 patients were with refractive anomaly myopia,whitch was divided I three groups:low,medium and high myopia. All patients were examined: ophtalmic measurements, field of vision, gonioscopy, echobiometry, OCT. Results were recorded in survey questionnaires, made for this study. Results: Patients who have myopia 5 times (Exp(B)=5.0 / 2.10-11.90 / p<0,001) have a significantly higher risk of developing glaucoma than patients without myopia. Patients who have high myopia o by 10,56 times (Exp(B)=10,56) have a significantly higher risk of glaucoma than patients without myopia, the impact of high myopia is significant / 95%Cl:2,67-41.78 / p<0.01. Patients who have medium myopia by 4.17 times (Exp(B)=4.17) have a significantly higher risk of glaucoma than patients without myopia, the impact of medium myopia is significant / 95%Cl:1,33-13-07 / p<0,05. Patients with low myopia by 3.06 times (Exp(B)=3,06) have a significantly higher risk of glaucoma than patients without myopia, the effect of low myopia is not significant / 95%Cl:0,94-9,97 / p>0,05 Conclusion: based on results of our study, there was a significant association between myopia and glaucoma. Patients who have myopia by 5 times have a significantly higher risk of developing glaucoma than patients without myopia. The study showed that patients with high and medium myopia had a significantly higher risk of glaucoma than patients without myopia.
Докторска дисертација одбранета во 2020 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Никола Пановски.
Keywords: myopia, glaucoma, connectivity, risk factors